The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.3389/fmicb.2017.01414
|View full text |Cite
|
Sign up to set email alerts
|

Antibody Detection, Isolation, Genotyping, and Virulence of Toxoplasma gondii in Captive Felids from China

Abstract: The felids are the only definitive hosts of Toxoplasma gondii, which could excrete oocysts into the environment and provide an infection source for toxoplasmosis in various warm-blooded animal species, particularly the captive felids that live close to human communities. The infection rate of the captive felids is a perfect standard in detecting the presence of Toxoplasma gondii oocysts in the environment. In this study, sera or tissue samples from zoo (1 young tiger, 2 adult tigers, 6 young lions), farm (10 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 41 publications
2
20
0
Order By: Relevance
“…This finding indicates that T. gondii oocysts are widely distributed in the country. This viewpoint was also verified by other reports ( Pan et al, 2017 ; Yang et al, 2017a ). Furthermore, the popularity of hotpot with undercooked mutton and pork increases the risk of human T. gondii infection in China, with other food animals also remaining as threats to public health ( Guo et al, 2015 ; Yang et al, 2017b ).…”
Section: T Gondii Prevalence and Risk Assessment In Food Ansupporting
confidence: 90%
“…This finding indicates that T. gondii oocysts are widely distributed in the country. This viewpoint was also verified by other reports ( Pan et al, 2017 ; Yang et al, 2017a ). Furthermore, the popularity of hotpot with undercooked mutton and pork increases the risk of human T. gondii infection in China, with other food animals also remaining as threats to public health ( Guo et al, 2015 ; Yang et al, 2017b ).…”
Section: T Gondii Prevalence and Risk Assessment In Food Ansupporting
confidence: 90%
“…In the present study, the seroprevalence of T. gondii in cattle was 1.93% (102/5292), which is lower than the rest of the world and China’s average infection rate. It is also lower than the seroprevalence of T. gondii in free-range chickens (18.86%, 132/700) [ 19 ], ostrich (10.20%, 20/197) [ 20 ], sheep (29.33%, 83/283) [ 21 ], swine (13.08%, 304/2325) [ 22 ], domestic cats (50%, 21/42) [ 23 ], and large cats (88.9%, 8/9) [ 24 ] in Henan Province. The maximum titer against T. gondii antibodies in dairy cattle was 3200 in this study.…”
Section: Discussionmentioning
confidence: 99%
“…have been registered in both captive and wild Siberian tigers, while G. duodenalis was found only in captive Siberian tigers (Han et al 2010;Li et al 2015;Seryodkin et al 2015). Toxoplasma gondii, another major zoonotic feline parasite (Elmore et al 2010), has been found both in captive and wild Siberian tigers (Domy & Fransen 1989;De Camps et al 2008;Seryodkin et al 2015;Yang et al 2017).…”
Section: Protozoans Of Siberian Tigersmentioning
confidence: 99%
“…and Toxoplasma gondii (Han et al 2010). T. gondii has been registered in captive Siberian tigers with a prevalence of 28.7% in the USA and 66.7% in Henan Province, China (Domy & Fransen 1989;De Camps et al 2008;Yang et al 2017). A Cystoisospora sp., molecularly identified as C. felis, has been recorded in the captive Siberian tigers from the Heilong- 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 (Han et al 2010).…”
Section: Protozoan Diversity In Captivitymentioning
confidence: 99%